Spatial distribution of suicides in Mato Grosso, Brazil, from 2008 to 2018 - Nascimento, Vagner Ferreira do; Lemes, Alisséia Guimarães; Machado, Lúbia Maieles Gomes; Silva, Tarciso Feijó da; Oliveira, Fernanda Rocha Anjos de; Terças-Trettel, Ana Cláudia Pereira; Luis, Margarita Antonia Villar (Acta Scientiarum. Health Sciences, 2023)
In the last few decades, it is believed that the state of Mato Grosso has been the stage of a substantial increase in suicide rates. However, the extension of this issue in the health regions of the state is still unknown. Therefore, the goal of this study was to analyze the spatial distribution of suicides in Mato Grosso, Brazil, from 2008 to 2018. This is an ecological study, with spatial-temporal distribution. Data collection took place in 2020 and was carried out in the Information System on Mortality for the period from January 2008 to December 2018. The suicide rates were calculated and smoothed using the empirical Bayes method, aided by the software GeoDa 1.12. To construct the maps, we used the software ArcGis 10.5. There were 1,977 recorded suicides in Mato Grosso, especially in males (79.3%), single (50.6%), from 20 to 29 years old (23.7%), brown (55.4%), with low educational levels (52.2%). Most suicides were carried out by intentional self-harm by hanging, strangulation and suffocation in the residence. The spatial-temporal distribution showed that the mesoregions North and Northeast had the highest rates, especially in cities in the health regions of Mid-Araguaia (for both sexes) and Garças Araguaia (for males). Suicides have followed a random, unequal pattern throughout Mato Grosso, but focused in areas of little development, showing the need to invest in health, and to strengthen and value policies to bring human resources to attend to these demands. The health care network must be structured to do so.